2008
DOI: 10.1089/pho.2007.2123
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Output Energy and Pulse Repetition Rate of the Er:YAG Laser on Dentin Ablation

Abstract: Objective: We sought to improve the efficiency of dentin ablation with the Er:YAG laser by investigating the effects of output energy and pulse repetition rate on ablation. Background Data: The Er:YAG laser is superior to other lasers in ablating dental hard tissues. However, the factors affecting the efficiency of ablation with an Er:YAG laser remain unclear. Methods: Fifty bovine root dentin plates were irradiated with an Er:YAG laser at an output power of 1.0 W, 1.5 W, or 2.0 W under a water spray while mov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Another study has investigated the influence of different output powers of Er:YAG, concluded that the output power is important in ablation efficiency and creates different shapes such as box, polygonal and bowel shaped architecture. 11 SEM images of experimental groups showed recrystallization areas around dentinal tubules. These areas form after that the laser irradiated peritubular dentin begins to cool down.…”
Section: Discussionmentioning
confidence: 94%
“…Another study has investigated the influence of different output powers of Er:YAG, concluded that the output power is important in ablation efficiency and creates different shapes such as box, polygonal and bowel shaped architecture. 11 SEM images of experimental groups showed recrystallization areas around dentinal tubules. These areas form after that the laser irradiated peritubular dentin begins to cool down.…”
Section: Discussionmentioning
confidence: 94%
“…A.Igarashi et al [ 4] illustrated that the depth and volume tended to increase at higher output energies and lower pulse repetition rate. Our study doesn't consider the effect of pulse repetition rate and it needs to be clarified in further studies.…”
Section: Methodsmentioning
confidence: 99%
“…The cross section of ablation crater presented a box type and the crater bottom was relatively flat (Fig.2 (b)). In the study by A.Igarashi et al [ 4], the ablated sites were divided into box, polygonal, and bowl types. The shape of the ablated site varied with the output power.…”
Section: Methodsmentioning
confidence: 99%
“…When studying different parameters and settings, Igarashi found that output energy had a much stronger effect on the depth and volume of ablation, when compared to the repetition rate [45]. He found that 120 mJ energy exclusively removed the demineralized tissue providing a more flattened surface, when compared to the higher energy outputs.…”
Section: Calculus Removalmentioning
confidence: 99%